Culture optimization for keratinase production by thermophilic bacillus licheniformis AAL3 in keratin waste biodegradation - Muharni, Muharni; Hasanah, Khairatul; Harvianti, Yuniar; Oktariansyah, Yadi (STKIP Persada Khatulistiwa Sintang, 2026)
Keratin waste is highly recalcitrant due to its complex protein structure, requiring efficient biodegradation strategies. This study aimed to evaluate and optimize keratinase production of thermophilic Bacillus licheniformis AAL3 isolated from the Air Putih hot spring, Lebong, Bengkulu. Qualitative keratinolytic activity was determined using feather meal agar, while quantitative enzyme activity was measured spectrophotometrically based on tyrosine release. The isolate exhibited a higher keratinolytic index (5.0) compared to B. licheniformis SCL2 (1.5). Quantitative analysis showed that AAL3 produced higher cell density (8.9 × 10? CFU/mL) and keratinase activity (1.0074 U/mL). Optimization studies revealed that maximum keratinase production occurred at 60 °C and pH 9. Among the tested carbon sources, 1% glucose resulted in the highest cell growth and enzyme activity, whereas 0.4% peptone was the most effective nitrogen source. The results demonstrate a strong positive correlation between bacterial growth and keratinase production. These findings indicate that B. licheniformis AAL3 has significant potential as a thermophilic keratinase producer for biotechnological applications, particularly in keratin waste biodegradation.